Some theorems of incremental thermoelectroelasticity (Archives of Mechanics - Test, 2010)
We extend to incremental thermoelectroelasticity with biasing fields certain classical theorems, which have been stated and proved in linear thermopiezoelectricity referred to a natural configuration. A uniqueness theorem for the solutions to the initial boundary value problem, the generalized Hamilton principle and the theorem of reciprocity of work are deduced for incremental fields, superposed on finite biasing fields in a thermoelectroelastic body.